Polymorphic differences in SOD‐2 may influence HCV viral clearance. Issue 6 (7th March 2014) - Houldsworth, Annwyne; Metzner, Magdalena; Shaw, Steve; Kaminski, Edward; Demaine, Andy G; Cramp, Matthew E
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) is a pathogen causing chronic hepatitis, cirrhosis, and liver cancer occurring in about 3% of the world's population. Most individuals infected with HCV develop persistent viremia. Oxidative stress may play an important role in the pathogenesis of a number of diseases including HCV infection and diabetes mellitus. Polymorphisms in the antioxidant genes may determine cellular oxidative stress levels as a primary pathogenic role in HCV and/or in its complications. Patients with HCV and normal, healthy controls were investigated for a superoxide dismutase (SOD‐2) polymorphism in the mitochondrial targeting sequence with Ala/Val (C‐9T) substitution. Polymorphisms in antioxidant gene SOD‐2 were carried out by PCR, restriction fragment length polymorphism assays and by polyacrylamide gel electrophoresis. For the SOD‐2 polymorphism, the RNA positive group showed a higher percentage of "CT" genotype than the RNA negative group (89.3% vs. 66.1%, P = 0.001, χ2 = 11.9). The RNA negative group had more TT genotypes than the RNA positive group (27.4% vs. 6.80%, P = 0.01, χ2 = 11.6). The exposed uninfected group had an increased frequency of the "CT" genotype (86.2% vs. 66.1%, P = 0.02, χ2 = 5.5). The RNA positives had a higher frequency of the "CT" from the normal controls (72.1% vs. 89.2%, P = 0.005, χ2 = 7.8). J. Med. Virol. 86:941–947, 2014. © 2017 Wiley Periodicals, Inc.